Prevalence of Fabry Disease among Patients with Parkinson’s Disease - Alexandra Lackova; Christian Beetz; Sebastian Oppermann; Peter Bauer; Petra Pavelekova; Tatiana Lorincova; Miriam Ostrozovicova; Kristina Kulcsarova; Jana Cobejova; Martin Cobej; Petra Levicka; Simona Liesenerova; et al. (Parkinson's Disease)
Background. An increased prevalence of Parkinson’s disease (PD) disease has been previously reported in subjects with Fabry disease (FD) carrying alpha-galactosidase (GLA) mutations and their first-line relatives. Moreover, decreased alpha-galactosidase A (AGLA) enzymatic activity has been reported among cases with PD compared to controls. Objective. The aim of our study was to determine the prevalence of FD among patients with PD. Methods. We recruited 236 consecutive patients with PD from February 2018 to December 2020. Clinical and sociodemographic data, including the MDS-UPDRS-III scores and HY stage (the Hoehn and Yahr scale), were collected, and in-depth phenotyping was performed in subjects with identified GLA variants. A multistep approach, including standard determination of AGLA activity and LysoGb3 in males, and next-generation based GLA sequencing in all females and males with abnormal AGLA levels was performed in a routine diagnostic setting. Results. The mean age of our patients was 68.9 ± 8.9 years, 130 were men (55.1%), and the mean disease duration was 7.77 ± 5.35 years. Among 130 men, AGLA levels were low in 20 patients (15%), and subsequent Lyso-Gb3 testing showed values within the reference range for all tested subjects. In 126 subsequently genetically tested patients, four heterozygous p.(Asp313Tyr) GLA variants (3.2%, MAF 0.016) were identified; all were females. None of the 4 GLA variant carriers identified had any clinical manifestation suggestive of FD. Conclusions. The results of this study suggest a possible relationship between FD and PD in a small proportion of cases. Nevertheless, the GLA variant found in our cohort is classified as a variant of unknown significance. Therefore, its pathogenic causative role in the context of PD needs further elucidation, and these findings should be interpreted with caution.